1980
DOI: 10.1002/hlca.19800630309
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the ESR. Coupling Constants of the [16]Annulene Radical Anion; Theoretical and Experimental Reinvestigation of the Excited States of [16]Annulene and its Mono‐ and Dinegative Ions

Abstract: SummaryThe problem of assigning the two small ESR. coupling constants of the [lblannulene radical anion to the two sets of four equivalent outer and inner ring protons is treated by three different semiempirical MO methods. All three methods indicate that the smaller coupling constant (0.743 Gauss) should be assigned to the inner protons, and the larger one (0.963 Gauss) to the outer ones. The electronic spectra of [ 16]annulene, its radical anion, and its dianion have been remeasured. Especially interesting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Two modifications of the original complete neglect of differential overlap/spectroscopic (CNDO/S) method were used, one due to Baumann and Oth and the other to Dick and Hohlneicher . Both of these calculations and also the LCOAO calculation 15 used the experimental geometry of 1 , and this was used for the LCOAO calculations on aza derivatives of 1 as well.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Two modifications of the original complete neglect of differential overlap/spectroscopic (CNDO/S) method were used, one due to Baumann and Oth and the other to Dick and Hohlneicher . Both of these calculations and also the LCOAO calculation 15 used the experimental geometry of 1 , and this was used for the LCOAO calculations on aza derivatives of 1 as well.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Annulenes have attracted much attention since the first report on [8]annulene in 1911 . Many efforts have been devoted to probing the (anti)aromaticity of [4 n ]annulenes by using NMR spectroscopy and computational methods. The addition of π-electrons to the [4 n ]annulenes that are antiaromatic in the Hückel sense has been carried out to alter their aromaticity and magnetic properties. Among the [4 n ]annulenes, studies on [12]annulenes and hetero[12]annulenes are very limited due to their decreased thermal stability. , Stevenson reported that [12]annulenes show diamagnetic properties 10a…”
mentioning
confidence: 99%